Income distribution and the fear of crime: Evidence from Germany - Michelle Acampora; Conchita D'Ambrosio; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We here explore the link between individual concerns about crime and the distribution of income in Germany. We make use of 1995-2017 microdata from the German Socio-Economic Panel (SOEP) to show that both individual polarization and relative deprivation have statistically-significant effects on reported concerns about crime, while relative satisfaction plays no role. At the aggregate level, the main driver is equally income polarization, whereas the standard measure of inequality, the Gini index, plays no significant role.
Keywords: I31; I32; D60; 330; concerns about crime; deprivation; inequality; polarization; SOEP